Factors that determine the success of self-isolation: A Qualitative Approach - Reni Aprinawaty Sirait; Putri Chairani Eyanoer (Gema Lingkungan Kesehatan, 2025)
The global challenges the during pandemic have created an urgent need for effective self-isolation programs to control the virus's spread. This study aims to identify the determinant factors of an Effective Self Isolation Program through a qualitative approach. The research is crucial as it provides insights into developing effective isolation strategies to handle the pandemic. Through qualitative data analysis, patterns were identified and it was found that factors such as public understanding of the importance of isolation, easy access to isolation facilities, and social support have a significant impact on the effectiveness of the Self Isolation Program. The research methodology involved in-depth interviews and qualitative data analysis. The findings of this research provide a deep understanding of the key success factors of the Effective Self Isolation Program. These findings are expected to guide policymakers in developing effective self-isolation programs and help suppress virus spread more effectively. The research results have demonstrated several determinant factors of an Effective Self Isolation Program as well as their important strategies and for minimizing the impact of a pandemic on the community. Patient understanding of self-isolation is still inadequate because patients tend to be more comfortable with self-isolation at home. Patient perception is also still lacking in realizing their health condition. Some patients feel dissatisfied with the attention and care provided by health workers so it is hoped that there will be increased communication and support from health workers that are more intense. Effective communication and caring family behavior are also needed to support the success of self-isolation.